A Comparison of IRT Observed Score Kernel Equating and Several Equating Methods - Wang, Shaojie; Zhang, Minqiang; You, Sen (Frontiers in Psychology, 2020)
IRT Observed Score Kernel Equating was evaluated and compared with Equipercentile Equating, IRT Observed Score Equating, and Kernel Equating methods by varying sample size and test length. In consideration that IRT data simulation might unequally favor IRT equating methods, Pseudo Tests and Pseudo Groups were also constructed to make equating results comparable with those from IRT data simulation. Identity Equating and Large Sample Single Groups rule were both set as criterion equating (or true equating) on which local and global indices were based. Results show that in random Equivalent Groups design, IRT Observed Score Kernel Equating is more accurate and stable than others. In Non-Equivalent groups with Anchor Test design, IRT Observed Score Equating shows lowest systematic and random errors among equating methods. Those errors decrease as shorter test and larger sample are used in equating, nevertheless effect of latter one is ignorable. No clear preference for data simulation method is found, though still affecting equating results. Preferences for true equating are spotted in EG. Finally, recommendations and further improvements are discussed.